The effects of gamat on nociceptive processing in the central nervous system - Yusof, Mohd Eidham (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2008)
Gamat or sea-cucumber is believed to have anti-inflammatory and antinociceptive property. The aim of this study was to investigate the effects of gamat on pain behaviour and c-fos expression in rats injected with formalin. Eight Sprague-Dawley male rats (220-300 gram) were allocated to two different groups. Gamat extracts from Holothuria spp. (4 mglkg) or distilled water was administered intraperitoneally immediately after intraplantar injection of 0.05 ml formalin (1 %). The rats' behaviour was recorded with a digital camcorder for one hour. The tape was viewed and behaviour score was tabulated at every minute and averaged at five minutes interval. The rats were sacrificed two hours after the formalin injection and the brains were removed. The brains were sliced into 20J.lm sections and examined for c-fos expression. Behaviour data were analysed using SPSS, version 13. Statistical analysis of pain behaviour was analysed using repeated measures analysis of variance (AN OVA) with post hoc Scheffe's test and significance level was taken as 0.05. The pain behaviour in the group receiving gamat was significantly (P<0.05 for each) reduced at 5 minutes (4 mg/kg gamat - 0.15 ± 0.3; control - 1.9 ± 0.82) and the differences were maintained until 35 minutes post formalin administration (4 mglkg gamat - 0 ± 0; control - 1.35 ± 0.93). C-fos expression in the thalamus was also reduced (mean=15.5) in the gamat group compared to the control group (mean=85). The gamat extracts from Holothuria spp has significantly suppressed the pain behaviour and c-fos expressions in formalin injected rat. Results from this investigation throw some light as to the possible use of gamat extract as an analgesic.